High performance computation of landscape genomic models including local indicators of spatial association. (28th November 2016) - Stucki, S.; Orozco‐terWengel, P.; Forester, B. R.; Duruz, S.; Colli, L.; Masembe, C.; Negrini, R.; Landguth, E.; Jones, M. R.; ,; Bruford, M. W.; Taberlet, P.; et al.
Abstract: With the increasing availability of both molecular and topo‐climatic data, the main challenges facing landscape genomics – that is the combination of landscape ecology with population genomics – include processing large numbers of models and distinguishing between selection and demographic processes (e.g. population structure). Several methods address the latter, either by estimating a null model of population history or by simultaneously inferring environmental and demographic effects. Here we presentsam βada, an approach designed to study signatures of local adaptation, with special emphasis on high performance computing of large‐scale genetic and environmental data sets.sam βada identifies candidate loci using genotype–environment associations while also incorporating multivariate analyses to assess the effect of many environmental predictor variables. This enables the inclusion of explanatory variables representing population structure into the models to lower the occurrences of spurious genotype–environment associations. In addition, sam βada calculates local indicators of spatial association for candidate loci to provide information on whether similar genotypes tend to cluster in space, which constitutes a useful indication of the possible kinship between individuals. To test the usefulness of this approach, we carried out a simulation study and analysed a data set from Ugandan cattle to detect signatures of local adaptation withsam βada, bayenv, lfmm and an F ST outlier method (FDIST approach inarlequin ) and compare their results.sam βada – an open source software for Windows, Linux and Mac OS X available athttp://lasig.epfl.ch/sambada – outperforms other approaches and better suits whole‐genome sequence data processing.